Optimization of Ultrasound Extraction of Cactus Pear (Opuntia ficus indica) Seed Oil Based on Antioxidant Activity and Evaluation of Its Antimicrobial Activity. (27th April 2017) - Ortega-Ortega, María de los Angeles; Cruz-Cansino, Nelly del Socorro; Alanís-García, Ernesto; Delgado-Olivares, Luis; Ariza-Ortega, José Alberto; Ramírez-Moreno, Esther; Manríquez-Torres, José de Jesús
Abstract : The purpose of the present study was to determine the optimal ultrasound conditions (amplitude level and time) for the extraction of cactus pear seed oil with the highest antioxidant activity using a closed system. Seed oil was analyzed for yield, antioxidant activity by ABTS and DPPH, and antimicrobial activity. Conventional extraction methods were assessed for comparison. Amplitude level significantly affected antioxidant activity in linear terms ( p < 0.0001 DPPH and p < 0.001 ABTS, resp.) so, at lower amplitudes, the higher antioxidant activity was achieved. The optimum ultrasound extraction conditions were of 78% amplitude for 10 min and yielded antioxidant activity values of 66.25 mg AAE/100 g and 289 µ mol TE/100 g for ABTS and DPPH, respectively. Compared with conventional extraction methods, ultrasound exhibited lower oil yield and antioxidant activity but had the potential to achieve comparable results if multiple ultrasound extractions are performed in the time needed by conventional methods. Seed oils showed similar antimicrobial activity despite the extraction method and were more effective against Escherichia coli . The results demonstrated that ultrasound can be an alternative extraction method of seed oils from fruits such as cactus pear.